Pilot Testing the Internal Structure of the Multicultural Competency Scale for Prospective Teachers - Wahyu Widodo; Sugiantoro Sugiantoro (Mitra Edukasi dan Publikasi, 2026)
Assessing pre-service teachers’ multicultural competence is fundamental to actualizing inclusive education, yet doing so requires robust psychometric tools. This study evaluates the construct validity of a Multicultural Competence Scale using Confirmatory Factor Analysis (CFA). Following rigorous preliminary diagnostics to ensure data suitability, the structural model was evaluated for overall fit, validity, and reliability. While the overarching measurement model demonstrated a robust structural foundation, localized vulnerabilities emerged within the awareness dimension. Specifically, items A1 and A6 failed to reach the necessary factorial thresholds (loadings < 0.30), signaling contextual and linguistic misalignments that require targeted revision. Ultimately, these findings underscore a critical methodological tension: the need to balance comprehensive construct representation with item efficiency. This research establishes an empirical baseline for optimizing the instrument’s cultural sensitivity and structural integrity prior to large-scale application.